An Active Proximity Warning System For Surface And Underground Mining Applications - W. H. Schiffbauer (The National Institute for Occupational Safety and Health (NIOSH))
NIOSH has developed an active proximity warning system called HASARD (Hazardous Area Signaling and Ranging Device) for warning workers as they approach known dangerous areas around heavy mining equipment and other dangerous work zones. HASARD is composed of a transmitter and a receiver. The transmitter generates a 60-kHz magnetic field using one or more wire loop antennas. Each antenna is adjusted to establish a magnetic field pattern for each hazardous area. The receiver, worn by the worker, is a magnetic field strength meter. The received signal is compared against preset levels which are calibrated to identify levels of danger. The receiver outputs can include visual, audible, and vibratory indicators and it can also be made to disable machine functions. HASARD was field tested on a Joy 12 continuous miner, a Komatsu 210 M Haulpak, and on a highwall launch vehicle. Slight modifications were made for each application. HASARD provided warnings as designed and proved to be rugged enough to withstand the harshest of production environments.